Diagnosis of Transmissible Venereal Tumor (TVT) in dogs (canis lupus familiaris) using the "imprint" method - Silva, Lidiely Pereira da; Souza, João Gustavo da Silva Garcia de; Lopes, Thiago Vaz; Muniz, Igor Mansur; Schons, Sandro de Vargas; Souza, Fernando Andrade (Research, Society and Development, 2022)
The Transmissible Venereal Tumor (TVT) is a common neoplasm among dogs, which rarely develops metastases, it is classified in the group of round cell tumors. This tumor is more commonly observed in young animals of different breeds, but it has a higher incidence in stray animals that are in the sexually active phase, with no distinction between the sexes, being observed in both males and females. The cellular morphology of TVT is very characteristic, different from other tumors classified as round cells, which makes the diagnosis easier. The clinical diagnosis of this tumor, by means of physical examination, is very common, since in many cases the tumor is observed in the external genitalia of the affected animals, being facilitated the collection of material for cytological examination. If the animal does not present in the external genitalia, it will be necessary to collect material for histopathology. The objective of this study was to verify the efficiency of the "imprint" methodology to perform the diagnosis of this venereal tumor. This methodology is considered low cost, easy to perform and fast, which leads to an accurate diagnosis. The results found are indicative that the “imprint” methodology proved to be effective for the diagnosis of this neoplasm, even because the use of cytology in the case of round cells in many cases is more accurate than the diagnosis made by histopathological techniques. El Tumor Venéreo Transmisible (TVT) es una neoplasia común entre los perros, que rara vez desarrolla metástasis, se clasifica en el grupo de tumores de células redondas. Este tumor se observa con mayor frecuencia en animales jóvenes de diferentes razas, pero tiene una mayor incidencia en animales callejeros que se encuentran en fase de actividad sexual, sin distinción de sexos, observándose tanto en machos como en hembras. La morfología celular del TVT es muy característica, diferente a otros tumores clasificados como de células redondas, lo que facilita el diagnóstico. El diagnóstico clínico de este tumor, ...